LANGAR OTA MAUSOLEUM: HISTORY AND MODERN TIMES (Intent Research Scientific Journal, 2025)
The article analyzes the history of the Hazrati Langar Ota shrine in the medieval period of Central Asia, its creation, and its historical significance from a modern perspective.